Influencia de las estrategias de marketing digital en el comportamiento de compra de comida rápida en la empresa KFC en la zona de Lima Centro en tiempos de COVID-19 - Chaname Colfer, Jorge Luis (2022)
The present research aims to identify which of the digital marketing strategies used by Kentucky Fried Chicken (KFC) is the one that is having the greatest impact on the purchase decision of consumers considering the current environment of the COVID-19 pandemic. Email marketing and social media marketing will be taken into account for this study. It is proposed to determine which is the digital marketing strategy with a greater degree of influence on the purchase decision of the customers of the KFC company in the Central Lima area during the times of COVID-19. The approach with which the research has been designed is Quantitative, having a correlational transectional scope and a non-experimental design. The instrument used to establish the validity of the hypotheses was a survey applied to a sample of 196 people between men and women who are between the age range of 18 to 30 years and who reside in the districts belonging to the Central Lima area. After analyzing the results obtained from the instrument, it is concluded that the digital marketing strategy with the most degree of influence on the purchase decision of customers is social media marketing, with 87.5% of the respondents indicating this.